2023
DOI: 10.1002/brb3.3136
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of the brain: Focus on the essential role of Piezo1‐mediated mechanotransduction in the CNS

Abstract: BackgroundThe brain is a highly mechanosensitive organ, and changes in the mechanical properties of brain tissue influence many physiological and pathological processes. Piezo type mechanosensitive ion channel component 1 (Piezo1), a protein found in metazoans, is highly expressed in the brain and involved in sensing changes of the mechanical microenvironment. Numerous studies have shown that Piezo1‐mediated mechanotransduction is closely related to glial cell activation and neuronal function. However, the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 200 publications
0
1
0
Order By: Relevance
“…Tenascin-C promotes cellular tension and regulates various other mechanical properties of the ECM (Midwood and Schwarzbauer, 2002; Miroshnikova et al, 2016; Saupe et al, 2013). Mechanosensitive ion channels like Piezo receptors, which microglia express, respond to mechanical activation with changes in Ca ++ ion influx that alter intracellular second messenger pathways (Procès et al, 2022; Zheng et al, 2023), and this signaling axis has been shown to promote microglia phagocytosis of amyloid plaques (Hu et al, 2023). The observation that tenascin C was the only matrisome protein to significantly decrease in the aged midbrain and striatum may suggest that it is a driver of secondary increases in other ECM protein and hyaluronan abundance, possibly through changes in mechanical signaling associated with tenascin deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Tenascin-C promotes cellular tension and regulates various other mechanical properties of the ECM (Midwood and Schwarzbauer, 2002; Miroshnikova et al, 2016; Saupe et al, 2013). Mechanosensitive ion channels like Piezo receptors, which microglia express, respond to mechanical activation with changes in Ca ++ ion influx that alter intracellular second messenger pathways (Procès et al, 2022; Zheng et al, 2023), and this signaling axis has been shown to promote microglia phagocytosis of amyloid plaques (Hu et al, 2023). The observation that tenascin C was the only matrisome protein to significantly decrease in the aged midbrain and striatum may suggest that it is a driver of secondary increases in other ECM protein and hyaluronan abundance, possibly through changes in mechanical signaling associated with tenascin deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…At present, the studies on MSCs in cerebral physiological processes dependent on applying modulators or genetic knockdown systems. 77 Given that MSCs like Piezo1 also participate in many complex processes that is usually transient and could not be interrogated through current strategies, such as learning and memory, in which the real‐time recording of MSC‐dependent neuronal activities is necessary. 78 Using strategies such as genetically encoded fluorescent reporter of piezo1, 79 as well as the in vivo microscopic or mesoscopic imaging, it might be helpful to study the complicated MSC functions in more depth.…”
Section: Functional Roles Of Mscs In the Cerebral Neurophysiological ...mentioning
confidence: 99%
“…Piezo1 is a nonselective cation ion channel and is expressed in various tissues ( Qin et al, 2021 ). It is known as the largest pore-like ion channel at ~300 kDa and also as a stretch activated ion channel (SAC) ( Zheng et al, 2023 ). Piezo1 is found integrated into cell membranes or ‘membrane blebs’, sometimes where integrins and ECM form adhesion sites ( Lai et al, 2022 ).…”
Section: An Overview Of Mechanotransductionmentioning
confidence: 99%